Evaluation of the Ionic Strength in the Preparation of Nanoparticles based on Chitosan - Castillo, Eileen V.; Oppliger, Diego Esteban; Luengo, Javiana Elizabeth; Pinto, Rayen Andrea; Villagra, Jose Andres; von Plessing, Carlos Guillermo (Drug Delivery Letters, 2017)
Background and Objective: Chitosan is a polymer widely used in the pharmaceutical industry. It is capable of interacting with sodium tripolyphosphate (TPP) forming nanoparticles (NPs) from the process of ionic gelation. This process uses factors that allow modulating the size of the NPs to be obtained. One of these factors is the incorporation of modifying agents of the ionic strength in the medium in order to obtain more stable and smaller NPs. Methods: A study of different salts was carried out. These were incorporated into the medium in concentrations that ranged between 0.05 M and 0.1 M. The characterization of NPs was performed by means of dynamic light scattering and transmission electron microscopy. Results: The salts that could decrease the size of the NPs less than 100 nm were NaCl, KCl and Na-HCO3, finally selecting NaCl as modifier agent of the ionic strength. Subsequently, the elaboration process of Chitosan NPs was optimized by means of an experimental design, being finally obtained particles with an average submicron diameter of 64.5 ± 1.8 nm, with irregular shape, smooth surface and a positive zeta potential of 32.6 ± 3.9 mV. Conclusion: In the analysis of salts it was possible to identify that only NaCl and NaHCO3 were capable of decreasing the size of chitosan NPs under 100 nm, obtaining particles of irregular shape and smooth surface.
Keywords: Nanoparticles